Selective Exercise of Discretion in Disability Insurance Awards - Pilar Garcia-Gomez; Pierre Koning; Owen O'Donnell; Carlos Riumallo Herl (Institute of Labor Economics (IZA), 2023)
Variation in assessor stringency in awarding benefits leaves applicants exposed to uninsured risk that could be systematic if discretion were exercised selectively. We test for this using administrative data on applications to the Dutch disability insurance program. We find that discretion is more often exercised in favor of lower-waged applicants. Pre-disability wages drop discontinuously just above disability thresholds for entitlement to partial benefits. Assessors are more likely to discard the highest-paying algorithm-generated job matches that determine earnings capacity and entitlement when evaluating lower-waged applicants. While these applicants benefit on average, they are exposed to greater risk from between assessor variation.
Keywords: D73; H42; H55; 330; disability insurance; screening